STIMULATED PLATELETS RELEASE AMYLOID β–PROTEIN PRECURSOR - Cole, Gregory M. (1990)
Human platelets can be stimulated by thrombin or ionomycin to secrete soluble truncated amyloid β–protein precursor and particulate membrane fragments which contain C-terminal and N-terminal immunoreactive amyloid β–protein precursor. This suggests a possible circulating source of β–protein in serum which may play a role in the formation of amyloid deposits. The release of soluble amyloid β-protein precursor could be involved in normal platelet physiology.